Difficult choices Taiwan's quest for security and the good life - Bush, Richard C. 1947- (Brookings Institution Press, 2021)
Front Cover -- Title Page -- Copyright Information -- Table of Contents -- Acknowledgments -- Notes on Terminology -- Introduction -- Popular Attitudes in Taiwan: A Preliminary Baseline -- Taiwan's Government Budget -- Taiwan's Economy -- Taiwan's Energy Policy -- The Politics of Taiwan's Past -- Beijing's Taiwan Ambition -- Taiwan's Search for Security -- Taiwan's Military Defense -- Taiwan's Political Defense: National Indentity -- Taiwan's Political Defense: The State -- The PRC's Asymmetric Offense -- Taiwan's Democratic System -- United States Policy -- What to Do? -- Notes -- Index -- Back Cover.
Description based on publisher supplied metadata and other sources
Keywords: Taiwan-Foreign relations-China; China-Foreign relations-Taiwan; National security-Taiwan